Microstructure and segregation behaviour of directionally solidified tungsten bearing 25Cr-35Ni-Nb heat-resistant stainless steels. (4th March 2017) - Attarian, Mitra; Karimi Taheri, Ali; Varahram, Naser; Davami, Parviz
Abstract: Two series of heat-resistant 25Cr-35Ni-Nb stainless steels with tungsten addition and Nb/C ratio of ≈2.6 and 3.9 were directionally solidified under two cooling rates of 23–6 °C s −1, respectively. EDS analysis, electron backscatter diffraction (EBSD), differential thermal analysis (DTA) and field emission scanning electron microscopy (FESEM) tests were carried out to show that tungsten as a carbide phase nucleant promoted weak coupled eutectic growth of γ / M7 C3 and decreased the lamellar eutectic colonies. Substantial negative segregation of Ni and Fe and positive segregation of Nb and Cr in tungsten-bearing alloys stimulated the γ/M23 C6 reaction and the M23 C6 possessed a dendritic morphology. Two morphologies of MC carbides consisted of Widmanstätten and dendritic with a wavy surface were detected depending on the cooling rate and tungsten addition. The partition coefficient of Nb was determined as 0.31 and 0.52 for the alloy with and without tungsten, respectively.